INTRODUCTION WEB APPLICATION NAMES ANIMALS IN Japanese language FOR BASIC SCHOOL STUDENTS USING Macromedia Dreamweaver 8.0 - Defry Irsan Amanda Nurlette (Jurnal Sistem Informasi, 2007)
Internet now becomes a choice to be the most effective in disseminating information, because the Internet has a range of very large networks. One of the information received great places on the Internet include information relating to education. This information is conveyed through one of the storage media of information on the Internet Website. Scientific writing is trying to explain how the development of a web page on the introduction of animal names for the Japanese-language primary school students. Starting from the design stage of the design, manufacture to the website ready published on the Internet. All were created using Macromedia Dreamweaver software 8.0